2020
DOI: 10.1177/0972266120966211
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of Climate-resilient Agriculture: A Review of Studies and Imperatives for Empirical Research in India

Abstract: Globally, climate change impacts are manifold, severely affecting the agriculture sector. Climate-resilient agriculture (CRA) is viewed as a panacea for overcoming the adverse effects of climate change on agriculture. This article critically reviews the literature on CRA to delineate the emerging patterns of climate-resilient agriculture. It explores multiple dimensions of CRA as related to practices, technologies, policies, innovations and interventions across different parts of the world. In the end, a schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 77 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…For example, a study conducted by the International Food Policy Research Institute (IFPRI) in Kenya found that farmers who sold livestock were more likely to adopt new agricultural technologies (Adato & Meinzen-Dick, 2002), such as tractors and plows, compared to farmers who did not sell livestock (Adato & Meinzen-Dick, 2002). Another study, conducted by the World Bank in India, found that livestock sales were positively associated with the adoption of agricultural machinery, particularly in regions where livestock farming was an important source of income (Viswanathan et al, 2020). This research highlights the importance of livestock sales as a source of income and capital for farmers, and the role they play in promoting the adoption of agricultural machinery.…”
Section: Livestock Salesmentioning
confidence: 70%
“…For example, a study conducted by the International Food Policy Research Institute (IFPRI) in Kenya found that farmers who sold livestock were more likely to adopt new agricultural technologies (Adato & Meinzen-Dick, 2002), such as tractors and plows, compared to farmers who did not sell livestock (Adato & Meinzen-Dick, 2002). Another study, conducted by the World Bank in India, found that livestock sales were positively associated with the adoption of agricultural machinery, particularly in regions where livestock farming was an important source of income (Viswanathan et al, 2020). This research highlights the importance of livestock sales as a source of income and capital for farmers, and the role they play in promoting the adoption of agricultural machinery.…”
Section: Livestock Salesmentioning
confidence: 70%
“…Climate change is also associated with increased land degradation, particularly soil salinization. Due to the predicted impact of climate change on the ability to produce food crops, there is an urgent need to improve the resilience and productivity of these crops to better suit the new climate (ABARES, 2021; Gowda et al., 2018; Viswanathan et al., 2020).…”
Section: Impact Of Climate Change On Crop Productivitymentioning
confidence: 99%
“…Especially for rice farmers, the government has provided fertilizer subsidies which are distributed to villages in East Java Province. But whether this is a benefit that can be felt by farmers is still a debate among the opinions of farmers personally (Maulana, 2016;Viswanathan et al, 2020). In the short-term, inflation in this case has a negative effect.…”
Section: Farmer's Term Of Tradementioning
confidence: 99%